2021
DOI: 10.1111/mec.15978
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the “world’s only alpine parrot”: Genomic adaptation or phenotypic plasticity, behaviour and ecology?

Abstract: Climate warming, in particular in island environments, where opportunities for species to disperse are limited, may become a serious threat to cold adapted alpine species. In order to understand how alpine species may respond to a warming world, we need to understand the drivers that have shaped their habitat specialisation and the evolutionary adaptations that allow them to utilize alpine habitats. The endemic, endangered New Zealand kea (Nestor notabilis) is considered the only alpine parrot in the world. As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 166 publications
0
18
0
Order By: Relevance
“…Although it is difficult to precisely pinpoint the driver of past population fluctuations, we form a number of hypotheses mostly based on correlations with volcanic activity. To date, few studies have used whole-genome data to investigate the longer-term demographic histories of New Zealand avian species, and those that have, have focussed on glaciation as a major influence [50][51][52]. As more genomes from a wider range of New Zealand species are made available, it will be possible to test whether volcanic eruptions may have also been a previously overlooked major evolutionary force shaping the biota of New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is difficult to precisely pinpoint the driver of past population fluctuations, we form a number of hypotheses mostly based on correlations with volcanic activity. To date, few studies have used whole-genome data to investigate the longer-term demographic histories of New Zealand avian species, and those that have, have focussed on glaciation as a major influence [50][51][52]. As more genomes from a wider range of New Zealand species are made available, it will be possible to test whether volcanic eruptions may have also been a previously overlooked major evolutionary force shaping the biota of New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…The consensus sequence was transformed to fastq format with vcfutils.pl vcf2fq keeping loci with read depth between 66× and 400× (average depth was 200×). We ran PSMC v0.6.5-r67 with parameter –p 4+30*2+4+6+10 and 100 bootstraps based on previous studies done for birds [ 69 , 70 ]. Results were plotted assuming a generation time of 3.17 years [ 71 ] and mutation rate of 3.44 × 10 –9 per generation (estimated for another passerine, the medium ground finch, Geospiza fortis [ 69 , 72 ]).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Landscape genetics was also used to study the historical and current distributions of the Crimson Rosella Platycercus elegans complex, showing that population expansion followed by secondary contact and hybridization might be responsible for their present genetic structure [207]. A recent study looked at functional genomic differences between the alpine Kea and the forest adapted Kākā in New Zealand, and showed that these adaptations are not driving the ecological differentiation between the two species [208].…”
Section: Molecular Ecology and Landscape Geneticsmentioning
confidence: 99%